2020
DOI: 10.3389/fpls.2020.592540
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Auxin Content Contributes to Larger Size of Apple Fruit

Abstract: Fruit size is an important economic trait that is controlled by multiple genes. However, the regulatory mechanism for fruit size remains poorly understood. A bud sport variety of “Longfeng” (LF) apple (Malus domestica) was identified and named “Grand Longfeng” (GLF). The fruit size of GLF is larger than that of LF, and both varieties are diploid. We found that the cell size in GLF fruit was larger than that of LF. Then, we compared the fruit transcriptomes of the two varieties using RNA-Seq technology. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 48 publications
(69 reference statements)
1
23
0
2
Order By: Relevance
“…This gene is expressed during cell division and cell expansion, consistent with a potential role in the control of fruit size ( Devoghalaere et al, 2012 ). Consistently, transcriptome analysis of “Longfeng” apple and its large-fruited bud sport variety “Grand Longfeng” showed that most of the differential genes were related to auxin signaling, including the auxin synthetic genes MdTAR1 and MdYUCCA6 ( Bu et al, 2020 ). These results suggested that auxin played a critical role in trait development of single fruit weight in apple.…”
Section: Apple Fruit Appearance Qualitymentioning
confidence: 83%
“…This gene is expressed during cell division and cell expansion, consistent with a potential role in the control of fruit size ( Devoghalaere et al, 2012 ). Consistently, transcriptome analysis of “Longfeng” apple and its large-fruited bud sport variety “Grand Longfeng” showed that most of the differential genes were related to auxin signaling, including the auxin synthetic genes MdTAR1 and MdYUCCA6 ( Bu et al, 2020 ). These results suggested that auxin played a critical role in trait development of single fruit weight in apple.…”
Section: Apple Fruit Appearance Qualitymentioning
confidence: 83%
“…Gradually, people perceived that it impacted a variety of physiological activities in plants, including senescence controlling, responses to abiotic stress and pathogens, formation of fruits, establishment and maintenance of cell polarity, apical dominance, phototropism, geotropism, etc. [ 4 , 5 , 38 , 39 , 40 , 41 ]. Auxin is synthesized in immature tissues such as tender leaves, cotyledons, and roots [ 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Auxin primarily originates from Greek, meaning growth [ 1 ]. It is irreplaceable during plant growth and development, which influences plant apical growth, axillary bud formation, floral organ development, and root development [ 2 , 3 , 4 , 5 ]. On the cell level, auxin is competent in changing the plasticity of plant cells, facilitating cells to differentiate and elongate.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the IAA concentration in the ‘O’Neal’ hypanthium maintained a relatively low level, rapidly increased beginning in the early cell expansion phase, and reached a relatively high level during maturation ( Figure 2C ). Bu et al (2020) reported that higher endogenous IAA was synthesized by a larger apple cultivar, and exogenous 1-naphthylacetic acid (NAA) treatment significantly increased fruit mass, whereas 2,3,5-triiodobenzoic acid (TIBA, an inhibitor of auxin polarity transportation) significantly decreased fruit mass. Therefore, high-level endogenous auxin in blueberry fruits might promote fruit cell expansion (not cell proliferation) and result in the production of larger fruits.…”
Section: Discussionmentioning
confidence: 99%